STRATEGIES AND INNOVATIONS IN THE MANAGEMENT OF ECONOMIC SYSTEMS: UKRAINIAN EXPERIENCE, RESPONSES TO CONTEMPORARY CHALLENGES - Svitlana Oneshko; Viktoriia Ivanova; Yevhenii Taran; Larysa Shypilova; Nataliia Sulima (Фінансово-кредитна діяльність: проблеми теорії та практики)
Ukraine is currently facing an acute issue of economic recovery, as the country seeks to emerge from the devastating effects of the global pandemic and level out and overcome the negative impact of the intensification of military operations on its territory. Given the above, the purpose of the article is to study Ukraine's experience in strategic management of economic systems, taking into account the existing experience and accumulated practices, as well as to substantiate proposals for the development and implementation of progressive, innovative tools of public management in accordance with the challenges of our time. Methods - deduction, induction, analysis, synthesis, dialectical logic, system and dynamic analysis, software modelling. Through the prism of historical retrospectives, the practices accumulated in the country of designing strategies of economic development in the institutional, organizational and substantive context are described. The structurization and detailed elaboration of different archetypes of state economic management, and formalized guiding principles which should form the basis of the elaboration and realization of the strategy of economic systems development have been presented. Separate attention is paid to the disclosure of the content of the components of the innovative platform of value creation, which should form the basis of strategic management of economic systems in Ukraine. The scientific novelty proved that the basis of strategic management of the development of economic systems of Ukraine at the present stage should be the archetype of "centralized and global management", which should be based on an innovative platform of value creation, by supporting three key sectors of economic progress: society, industry and management. The conclusions obtained in the study can be used by the Government of Ukraine and responsible institutions, as well as the business environment in justifying the structural content of the model of strategic management of progressive economic development by assessing the new challenges generated by the challenges of our time. For the achievement of efficiency of management of strategic development of economic systems in Ukraine, it is necessary to provide a synergy of state institutions, representatives of business, and the public.